PENDAFTARAN ONLINE SMP IT USWATUN HASANAH SEMARANG BERBASIS WEB MOBILE (Information Technology and Telematics, 2014)
Abstract-the number of smartphone users automatically create the rise of smartphone Internet users. Increased access to the Internet has led to new cultures and needs, among others, is the availability of a website that still look elegant even opened with the mobile phone. Or in other words the availability of the website responsive screen size mobile phone, it can be applied the Semarang SMP IT UswatunHasanah new student registration process is done by using the smartphone online for more practical compared to using a PC / Computer. purpose of this research is to design and build an online registration system android mobile web-based school that will be able to facilitate students and parents in the registration process without using a computer. In this research, the author uses the method prototype. To use the programming language PHP programming language and MySQL database. This research resulted in new student enrollment applications online at SMP IT UswatunHasanah Semarang-based mobile web that can be used by prospective students to ease the process of registration of new students at the junior IT UswatunHasanah Semarang. This application can be run on mobile devices that have android operating system. Keywords: online registration, school registration application online, web mobile. Abstrak - Naiknyapenggunasmartphoneotomatismembuatnaiknyapengguna internet dari smartphone.Meningkatnyaakses internet inimenimbulkanbudayadankebutuhanbaru, antara lain adalahtersedianya website yang tetaptampileleganwalaupundibukadengan mobile phone tersebut. Ataudengan kata lain tersedianya website yang responsive terhadapukuranlayar mobile phone, hal ini dapat di terapkan Pada SMP IT Uswatun Hasanah Semarangproses pendaftaransiswabarudilakukandengancaraOnline menggunakan smartphone agar lebih praktis di bandingkan menggunakan PC/Komputer.   tujuan penelitian ini adalahmerancangdanmembangunsistempendaftaran online sekolahberbasis web mobile android yang akandapatmempermudahsiswamaupunorangtuadalam proses pendaftaran tanpa menggunakan komputer. Dalampenilitianini, penulismenggunakanmetodeprototype. UntukbahasapemrogramanmenggunakanbahasapemrogramanPHPdan database MySql. Penelitianinimenghasilkanaplikasipendaftaransiswabaru online di SMP IT Uswatun Hasanah Semarang berbasis web mobile yang dapatdigunakanolehcalonsiswauntukmempermudah proses pendafataransiswabarupada SMP IT Uswatun Hasanah Semarang. Aplikasiinidapatdijalankanpadaperangkat mobile yang mempunyaisistemoperasi android. Kata Kunci :pendaftaran online, aplikasipendaftaran online sekolah, web mobile.